Association of GSTM1 and GSTT1 polymorphisms with reproductive health outcomes in women beedi rollers exposed to unburnt tobacco dust - Racharla, Spandhana; Sultana, Shehnaz; Reddy, P. P. (International Journal Of Community Medicine And Public Health, 2024)
Background: Beedi rolling, a labour-intensive activity mainly done by women in India, exposes workers to tobacco dust, leading to various health issues. This study examines the prevalence of GSTM1 and GSTT1 genotypes and their association with reproductive health in beedi rollers. Methods: The study comprises 500 women beedi rollers (BR) and 500 non-beedi rollers (NBR). A face-to-face interview was conducted with them to collect information on the reproductive outcome. GSTM1/T1 polymorphisms were studied using polymerase chain reaction. Tobacco exposure was estimated by serum nicotine metabolite levels through LC-MS. Results: There is a significant increase in reproductive complications in the BR group compared to the NBR. Null genotypes of both genes were significantly high in the BR group. Nicotine metabolite levels were significantly elevated in the BR group compared to NBR. Increased incidences of miscarriages and oligomenorrhea were significantly associated with the null genotypes of both genes. Conclusions: These findings suggest that genetic predisposition, combined with tobacco exposure, enhances health risks.